(untitled) (Eduscotech, 2023)
This study aims to analyze the research management standards implemented at Yogyakarta State University and Universiti Utara Malaysia. Specifically, the study examines: (1) the research management standards applied in both universities, (2) the realization of research management standard achievements, and (3) the challenges encountered in the implementation of these standards. This research employed a mixed-methods approach using a comparative study design to identify similarities and differences in research management practices between the two institutions. The findings reveal that both universities adopt research management standards encompassing planning, organizing, implementation, monitoring, and evaluation. The realization of these standards is similarly supported by institutional research bodies operating under the direct supervision of the rector. Research management is coordinated by institutional leaders who are accountable to the rector. Challenges in implementation include administrative constraints, limited resources, and variations in policy execution. Overall, the study highlights that both institutions maintain structured research management systems, although improvements remain necessary to strengthen institutional research quality and performance.